2009
DOI: 10.1002/pon.1568
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patients' desire for psychological support: prevalence and implications for screening patients' psychological needs

Abstract: Objectives: To investigate cancer patients' desire for psychological support and to identify patients' sociodemographic, disease-related and psychological factors associated with this desire.Methods: The study is part of a multicenter, cross-sectional study assessing cancer patients' needs and desire for psychological support. Patients completed the Hospital Anxiety and Depression Scale, the Ways of Coping Checklist, the Cancer Rehabilitation Evaluation System and reported their desire for psychological suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

32
178
8
17

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(242 citation statements)
references
References 56 publications
32
178
8
17
Order By: Relevance
“…Many studies have shown the need for the cancer patient to receive psychological support (Ernstmann et al, 2009;Goldzweig et al, 2010). In a German study, 18.9% of patients indicated an unmet need for psychosocial support and 9.5% of patients were actually using psychosocial services; that need was higher in female patients (Merckaert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the need for the cancer patient to receive psychological support (Ernstmann et al, 2009;Goldzweig et al, 2010). In a German study, 18.9% of patients indicated an unmet need for psychosocial support and 9.5% of patients were actually using psychosocial services; that need was higher in female patients (Merckaert et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Reasons given were that they had no need (n 5 17), they found it too burdensome (n 5 16) or they had received psychosocial treatment previously (n 5 1) [23]. Merckaert et al (2009) examined predictors of desire for help. Younger people, working men and women receiving hormone therapy had a greater desire for psychological support [24].…”
Section: Discussionmentioning
confidence: 99%
“…However, in earlier studies [23,24], it has been noted that nurses of oncological and surgical patients also support the patient in a psychologically difficult life situation. The presence of other patients in the patient room may also affect the fact that nurses do not open a discussion on feelings and mood.…”
Section: Discussionmentioning
confidence: 99%